"The day after": The organizational consequences of innovation implementation in experimental schools. Issue 1 (1st February 2016) - Gilad-Hai, Smadar; Somech, Anit
Abstract : Purpose: – The purpose of this paper is to examine the implications of implementing innovation in experimental schools (focussing on R & D) for school effectiveness post-intervention (five years). Based on theoretical models of social exchange and "conservation of resources" (Hobfoll, 1989), the authors focussed on assessing the effects of implementing innovation on individual outcomes (strain) and school level outcomes (social cohesion, emotional conflict, organizational innovation). The authors compared three types of schools: schools that have completed the implementation process (after), schools still in the implementation process (during) and schools not participating in the implementation process (control group). Design/methodology/approach: – A sample of 75 schools (23 non-experimental, 25 during the experiment, 27 post-experiment) was used. Data were collected from teachers and principals to avoid a single source bias. Findings: – MANOVA analyses suggest that the process of implementation of innovation contributes to organizational effectiveness: differences were found between the control group and the two groups of experimental schools. The two groups of experimental schools showed higher levels of organizational innovation and social cohesion and lower levels of emotional conflict and strain as compared to the control group. Research limitations/implications: – This study concentrated on the question of the direct links between the study variables – the effects of the implementation of innovation on school functioning. It would be interesting to examine the limit conditions (encourage – discourage factors) for these relations. Practical implications: – Findings suggest that a structured process of implementing innovation contributes not only to the outcome of innovation in school, but also enhances overall school functioning. Originality/value: – Permits the authors to deepen the knowledge of the potential of organizational processes of innovation in schools over time (pre-during-post process).